Free seeds and food sovereignty: anthropology and grassroots agrobiodiversity conservation strategies in the US South - Brian C. Campbell; James R. Veteto (Journal of Political Ecology, 2015)
Neoliberal economic frameworks threaten the ability of marginalized people worldwide to grow, harvest, and access sufficient healthy food because they deny traditional collective seed ownership and preclude subsistence as a viable livelihood. Many internationally-oriented counter-responses work to reframe intellectual property law in favor of traditional farmers. In the United States, various grassroots agricultural biodiversity conservation projects designed to re-establish the control of open-pollinated seeds within communities have emerged with similar intent. This article situates and explores the role of open-pollinated seeds and agricultural biodiversity conservation strategies in local food sovereignty. The authors direct applied research projects that collaboratively document and disseminate open-pollinated seed varieties throughout the Southeastern United States with a specific focus on the Ozark Highlands and Appalachian Mountains. The research methods represent an activist anthropology—participant observation and ethnographic interviewing while collaboratively growing and sharing seed varieties with local farmers, gardeners, seed-savers, and activists—with the explicit purpose of forging more sustainable, integrated, and sovereign local food systems.